Market opportunities for selected indigenous fruits and vegetables in northern Vietnam: A survey report - Le, Nhu Thinh; Nguyen, Thi Tan Loc; Nguyen, Thi Sau; Nguyen, Manh Dat; Hoang, Ky The; Nabuuma, Deborah; Ghione, Andrea; Swaans, Kees (2024)
An exploratory survey that sought to (i) identify local/indigenous fruits and vegetables used in local recipes used in the tourism industry and bearing a significant and cultural meaning for the local communities; (ii) Determine the production methods of the selected local/indigenous fruits and vegetables, and opportunities to yield, quality, environmental footprint and safety; (iii) identify of business models particularly between the tourism sector entry points; and (iv) Explore the potential for certification related to indigenous fruits and vegetables in Northern Vietnam